(untitled) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
Community empowerment is one of the impacts produced by the tourism sector. On the next trip, the development of tourism also stimulated the emergence of tourism-supporting industries such as transportation, culinary, souvenirs, and crafts. In an effort to create sustainable tourism, the presence of the batik craft industry as a tourism supporter is very much needed. Talking about green environmental issues, the batik industry also has the potential to threaten environmental sustainability. Referring to this, management needs to pay attention to and prepare various things that support business sustainability. Green human resources are interpreted as an effort to maximize their potential. This step is an organizational strategy for responding to green challenges and performance. This study will look at the extent to which green human resource management practices support the management of the management business. A qualitative research design through a literature study was used with reference to existing provisions. The results of the study explain that green human resource practices are able to support improving the quality of human resources. Some efforts that can be made include searching for human resources through screening, providing training and optimizing human resources, conducting human resource assessments, and providing appropriate rewards for the performance provided.